Parâmetros bioquímicos indicadores da qualidade do ar das espécies Licania tomentosa (Benth.) e Bauhinia forficata (Link.) no biomonitoramento na Região da Grande Vitória, ES/Brasil - Maioli, Otávio Luiz Gusso (2006)
Parameters had been analyzed bioindicators as pH, acid ascorbic, index buffering capacity (BCI), activity of peroxidase, chlorophyll, A, B and β-carotene in order to relate the level of estress of 02 plants species with the tropospheric ozone concentration ambient in the region of Grande Vitória (RGV). The studied species had been Licania tomentosa (Benth.) and Bauhínia forficata (Link.). The concentrations of the parameters had been compared bioindicators in leves of the species between quarters with considerable indices of pollution (Enseada do Suá, Laranjeiras, Ibes) and the Ecological Reserve of Duas Bocas, considered as free region of the load of pollutants. For the RGV the maximum values of ozone (O3) for the period of exposition of 4 hours are 140 µg/m3 , and are above of the minimum values considered by Stern et al (1984) that they cause injuries to the vegetal species as vegetables, orquídeas and tobacco (59 µg/m3 ). 3 campaigns of analyses had been carried through biochemists (Outubro/Novembro/2003, Dezembro/2004 and Agosto/2005), where it was possible to verify the annual and seasonal influence of the stations of the year and ozone in the parameters biochemists. Ten different methodologies for the calculation of the ozone concentration had been implemented (average daily, average daily between 7:30h and 18:30h, daily average between 9:30h and 16:30h, horary mobile average for 4 hours of exposition, monthly average of the daily average, monthly average of the daily principle, SUM-0, AOT-40 and SUM-60, beyond the horary average). These methodologies can improve the answers on the impact of ozone in the alterations biochemists of vegetables. Moreover, the influence of the ground of the places in study was verified, carrying through an analysis of nutrients of soil in Dezembro/2003. Parameters bioindicators as pH, BCI, acid ascorbic, activity of peroxidase and total chlorophyll in the species Licania tomentosa and; pH, BCI, acid ascorbic, total chlorophyll and β-carotene in the species Bauhínia forficata, constitute indicating potentials of estress caused for the pollution of air, especially for ozone. The horary mobile averages for 4 hours of exposition and the AOT-40 if relate as well as some alterations biochemists in the species. Both the species have presented sensitivity to the atmospheric pollution through alterations observed in different parameters biochemists for different ozone concentrations.